expand it again
= sinx cos^2 y - cosxsinycosy + cosxcosysiny + sinxsin^2 y
= sinx(cos^2 y - sin^2 y)
= sinxcos(2y)
Simplify:
sin(x-y)cosy+cos(x-y)siny
= (sinxcosy-cosxsiny)cosy+(cosxcosy+sinxsiny)siny
= ???
What do I do next???
Please Help and Thank You
4 answers
when I substitue the x's and y's I get different answers.
do I need brackets on (sinxcosy-cosxsiny) and (cosxcosy+sinxsiny)?
could the next step be: sinxcosy-cosxsinycosy+cosxcosy+sinxsinysiny without the brackets? or would that be wrong?
do I need brackets on (sinxcosy-cosxsiny) and (cosxcosy+sinxsiny)?
could the next step be: sinxcosy-cosxsinycosy+cosxcosy+sinxsinysiny without the brackets? or would that be wrong?
found my error
2nd last line should have been
= sinx(cos^2 y + sin^2 y)
= sinx (1)
= sinx
2nd last line should have been
= sinx(cos^2 y + sin^2 y)
= sinx (1)
= sinx
thank you so much=)